DOUBLE-PARAMETER THRESHOLD AND ITS FORMATION MECHANISM OF THE COLLUVIAL LANDSLIDE: XINTAN LANDSLIDE, CHINA - Keqiang H.; Sijing W. (My University, 2006)
Data compiled from monitoring the displacement resulting from the Xintan landslide in China was analyzed. The stability of the demonstrated colluvial slope has a close correlation with two parameters, the velocity of the displacement and the angle of the surface vector. The stability trend can be described and evaluated by both the velocity of the displacement and the vector angles. The displacement vector angle, for which there is no substitute, serves as an explicit criterion for the stability of the slope, hence it is significant in the prediction of the catastrophic movement of landslides. A systematic analysis of the features of the vector angles of the surface displacement space and time was performed. The evolving mechanism of space-time and the characteristics of the displacement vector angles were deduced. On the basis of these deductions and by using principles of statistics, the double-parameter threshold for forecasting the stability of the colluvial slopes was established. According to the double-parameter threshold, a calculation and evaluation of stability was completed in terms of the monitoring data of the F-series of points on the Xintan slope. The forecast results coincided with the destabilized timetable, thus demonstrating that the double-parameter criterion has, to a certain extent, precision and practical application for forecasting of landslides.
Keywords: COLLUVIAL SLOPE; SURFACE DISPLACEMENT VECTOR ANGLE; DISPLACEMENT VELOCITY; SPACE-TIME CHARACTERISTICS; DOUBLE-PARAMETER THRESHOLD; XINTAN LANDSLIDE; CHINA SLOPE STABILITY